Counselling-in-continuum-modern solution to ‘Google’ patients? - Bahl, Ina; Khanna, Sanat Kumar (International Surgery Journal, 2021)
Aim of the study was to highlight the benefits, barriers and methodology pertaining to effective patient counselling. The modern-day patient is well informed and well aware of patient rights. The need of the hour is to implement management plans jointly agreed upon based on both scientific evidence and patient preference by proper patient counselling. The process of counselling represents a well-founded intervention made of a quality interaction between the counsellor and the patient. Effective communication is advantageous for both healthcare professionals in the form of a comprehensive medico legal document, as well as for the patient as it tends to allay fear of treatment, dissipate misconceptions garnered from half-baked knowledge off the internet, cementing a bond of trust between the two. Counselling forms should carry information pertaining to the details regarding the patient’s disease, treatment options, pros and cons with aids in the form of pictures, models and videos. Ample time should be spent on the patient’s doubts, without the use of medical jargons. Barriers to effective communication include physical, psychological, administrative or time conflicts. Upliftment from the quick sands of barriers to patient communication requires the introduction of a curriculum laying emphasis on sound communication skills right from the undergraduate stage. Furthermore, internet can be used to aid counselling in the form of legit informative portals wherein patients are able to gather correct information about their disease and prognosis as is the case with online healthcare communities.